Non-neuronal Role of Acetylcholinesterase in Bone Development and Degeneration - Luo, Xiaohe; Lauwers, Marianne; Layer, Paul G.; Wen, Chunyi (Frontiers in Cell and Developmental Biology, 2021)
Acetylcholinesterase (AChE) is an enzyme catalyzing the degradation of acetylcholine to regulate cholinergic signaling. The expression of acetylcholinesterase and other cholinergic components is not restricted to only brain and nerve tissues but can also be found in non-neuronal tissues like immune system and bone tissue. Primary identification of these components has been achieved. However, the information about their specific functions and underlying molecular mechanisms remains scattered. Here, the physiological process of bone development, homeostasis and degeneration are introduced. Next, the cholinergic system and its expression in bone tissue are documented. Among them, special attention goes to AChE, as the structure of this enzyme suggests diverse binding affinities, enabled by a peripheral site and a catalytic site. The peripheral site supports the non-enzymatic function of AChE in non-neuronal systems. Based on recent studies, the non-neuronal roles of acetylcholinesterase, both enzymatically and non-enzymatically, in bone development, homeostasis and degeneration are summarized briefly together with potential mechanisms to support these functions. We conclude that AChE may be a potential therapeutic target for bone diseases like osteoporosis.